2017
DOI: 10.1111/jon.12486
|View full text |Cite
|
Sign up to set email alerts
|

Cerebral White Matter Maturation Patterns in Preterm Infants: An MRI T2 Relaxation Anisotropy and Diffusion Tensor Imaging Study

Abstract: Background and Purpose-Preterm birth is associated with worse neurodevelopmental outcome, but brain maturation in preterm infants is poorly characterised with standard methods. We evaluated white matter (WM) of infant brains at term-equivalent age, as a function of gestational age at birth, using multi-modal MRI.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
26
1
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(39 citation statements)
references
References 35 publications
(44 reference statements)
4
26
1
2
Order By: Relevance
“…61 DTI values change with white matter maturation, thus the study population was restricted to term or near-term neonates. 62 Pseudo-normalization is noted to occur at approximately 8-10 days postinjury for ADC changes. 63 We plotted FA values according to day of MRI and found no difference between studies occurring prior to or after 10 days of life.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…61 DTI values change with white matter maturation, thus the study population was restricted to term or near-term neonates. 62 Pseudo-normalization is noted to occur at approximately 8-10 days postinjury for ADC changes. 63 We plotted FA values according to day of MRI and found no difference between studies occurring prior to or after 10 days of life.…”
Section: Discussionmentioning
confidence: 97%
“…There is increased attention in the literature to administering TH to late preterm neonates . DTI values change with white matter maturation, thus the study population was restricted to term or near‐term neonates . Pseudo‐normalization is noted to occur at approximately 8‐10 days postinjury for ADC changes .…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, recent research indicated less developed white matter at term equivalent age for PT infants born before 30 gestational weeks compared to PT infants born closer to term. 93 A graph theory framework uses advanced statistical modeling to demonstrate brain connectivity as a network of nodes (brain regions) and links (connections between regions) and describes patterns of network connectivity, including the direction and strength of modeled connections. 5,94,95 These studies provide converging evidence suggesting specialized structural network topology associated with prematurity that is characterized by reduced network integration (also referred to as efficiency) when compared to term-born equivalents.…”
Section: Atypical Brain Development Following Preterm Birthmentioning
confidence: 99%
“…Известно, что нарушения нормальных процессов миграции, миелиниза-ции и синаптогенеза у недоношенных детей приводят к когнитивным, моторным и пове-денческим дисфункциям. [38]. Поэтому ранняя диагностика имеет большое значение для предотвращения необратимых изменений тка-ней головного мозга.…”
Section: рис 11 (unclassified
“…В исследовании созревания головного мозга у недоношенных детей M. J. Knight и соавт. (2018) продемон-стрировали, что значения КФА у недоношенных детей, родившихся до 32 недели гестации зна-чительно ниже более поздних рожденных недо-ношенных и доношенных групп [38]. Аналогич-ные результаты были получены и F. Zhang с со-авт.…”
Section: рис 11 (unclassified